Водопоглощение каолинит-полимерными композитами - Федоренко, Ю.Г.; Розко, А.Н.; Туренок, О.Ч.; Дяченко, Е.В. (Мінералогічний журнал, 2010)
С использованием метода свободнорадикальной полимеризации акриламида в водных суспензиях каолинитов получены каолинит-полимерные композиты. Показано, что водопоглощение композитов практически не зависит от дисперсности и степени совершенства кристаллитов каолинитов и в значительной мере определено их структурно-механическими характеристиками и условиями проведения водопоглощения. З застосуванням методу вільнорадикальної полімеризації акриламіду у водних суспензіях каолінітів одержано каолініт-полімерні композити. Показано, що водопоглинання композитів практично не залежить від дисперсності та ступеня досконалості кристалітів каолінітів і значною мірою визначено їхніми структурно-механічними характеристиками й умовами проведення водопоглинання. Characteristics of polyacrylamide-clay composites (PCC) are determined by various factors, such as the type of the polymer, physico-chemical properties of clays and clay minerals, synthesis conditions. The characteristics of the organic component of PCC (polymer) are determined by the producer. The mineral component (clay minerals) has various physicochemical characteristics which influence the synthesis and PCC properties. Use of kaolins permitted to assess the impact of aggregate composition, dispersion and degree of structure perfection on PCC synthesis and properties. The authors studied water absorption by kaolin-polymer composites (KPC). Monomineral clays from Glukhovetske, Prosianivske and Glukhivske deposits, which have different cation-exchange capacity, dispersion and degree of crystalline structure perfection, were used for the synthesis. The organic component was presented by acrylamide monomers (AM) and the cross-linking agent for receiving the volume-linked polyacrylamide (PAA) — N,N — by methylenebisacrylamide (MBAA). The conditions remained constant through all the series of experiments. The ratio polyacrylamide : methylenebisacrylamid was 24 : 1. The amount of kaolin in the samples varied from 27 to 48 %. Water absorption was assessed by maximum degree of swelling of KPC samples in water. The initial mass of samples was 25 and 100 mg. Several methods of preparation of suspensions for polymerization were tested — mechanical activation of kaolin suspension, PAA solution or their mixture. It was found that water absorption does not depend on the method of preparation of the suspensions. From 8.6 to 14.5 % of AA are sorbed from 9.3 % AA solution by kaolins. Maximal sorption is observed on highly dispersed Glukhivske kaolin with low degree of structure perfection. The degree of swelling of air-dry KPC samples was shown to depend weakly on the nature of the kaolins, the degree of structure perfection and dispersion which depends on the size of crystallites. In the experiments with kaolins, which have low capacity of caution exchange their aggregate composition determined by structural-mechanical characteristics is the most important. Water absorption and the rate of swelling of the samples increase with an increase in temperature of synthesis. The degree of swelling of PAA in PCC samples was assessed. It was also practically independent of the nature of the kaolin and approached the values received by AA polymerization without contact with the mineral component.